1883 Mo. Laws 76 - (:unkn) unknown (My University, 1883)
An Act to Amend Section 1274, Article 2, Chapter 24 of the Revised Statutes of Missouri, Entitled "Of Crimes And Criminal Procedure" § 1274: Prohibited the carrying of a concealed fire arms, Bowie knife, dirk, dagger, slungshot, or other deadly weapon to a church, school, election site, or other public setting or carrying in a threatening manner or while intoxicated. Punishable by fine of $25-200 and/or by imprisonment up to 6 months.
Keywords: CARRY - CERTAIN PUBLIC PLACES; CARRY - CONCEALED